THE ROLE OF AI IN PERSONALIZED LEARNING - Sadriddinova Mashhura Uktam kizi; Khasanova Yulduz Mukhtor kizi (Bright Mind Publishing, 2025)
This article investigates the influence of Artificial Intelligence (AI) on personalized learning and its diverse effects on student engagement, management of cognitive load, and self-directed learning behaviors. A structured survey was conducted using a Telegram bot, targeting a random sample of 30 university students aged between 20 and 23. Participants provided their feedback on five detailed Likert-scale questions assessing their overall views, frequency of use, familiarity with tools, perceived effectiveness, and perspectives on the role of AI compared to human educators. The responses were coded (A=5 to E=1) and categorized based on the number of ‘very positive’ responses, leading to the identification of three groups: Strong Enthusiasts (n=6), Moderate Supporters (n=18), and Cautious Adopters (n=6). Key findings indicate that 80% of the participants have a positive outlook on AI-enhanced learning. On a quantitative basis, adaptive modules resulted in a 30% increase in lesson completion rates, automated feedback systems improved revision quality by 25%, and AI-driven scheduling tools enhanced weekly study time by 15%. These findings highlight AI’s potential to streamline personalized learning paths, minimize wasted time, and facilitate greater understanding. However, qualitative insights reveal apprehensions regarding possible overdependence and a decrease in critical thinking skills. The study concludes with suggestions for a blended teaching model that combines the advantages of AI with human-led education to maintain educational richness and interpersonal interaction.
Keywords: Artificial Intelligence; Personalized Learning; Adaptive Education; Cognitive Load Management; Automated Feedback; Learner Engagement; Self-Directed Study.